Cliffs test of English as a foreign language preparation guide - Pyle, Michael A. (Cliffs Notes, 1995)
It's Important to Prepare for the TOEFL This Cliffs Preparation Guide can help you score higher. It provides background and understanding of the TOEFL, which can help you take the test with maximum efficiencyand make the kind of score that can give you a wide choice of colleges or graduate schools. Our testing experts designed this Preparation Guide to help you get ready for the TOEFL while using your study time effectively. Right from the start, you'll find that it is thorough, concise, to the point and easy to understand. This Guide includes: Analysis of Each Type of Question and Explanation of the Most Successful Approaches to each area tested: Listening Comprehension, Structure and Written Expression, Reading Comprehension, and the Test of Written English (essay). Intensive Grammar Review, Exercises and Mini-Tests to guide and simplify your study. Six Full-Length Practice Tests that correspond to the actual TOEFL in type and number of questions. Answers and Explanations, Cross-Referenced to the Review, for each practice test. Self-Scoring Charts to analyze your performance on the sample tests. Two Audio Cassettes containing six Listening Comprehension sections for realistic test preparation. Complete Table of Contents and Index to help you quickly find what you are looking for. Be ready. Give yourself an edge in taking the TOEFL by using this Cliffs Preparation Guide. You'll be glad you did